Final Position Arbitration and Intertemporal Compromise - Dworkin, James B. (Relations industrielles / Industrial Relations, 1977)
This paper seeks to present further evidence from the realm of professional baseball in regard to Swimmer's criticism of final offer procedure.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z